2005
DOI: 10.1111/j.1365-3083.2005.01678.x
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Group IIA Phospholipase A2 and Complement in Killing of Bacteria by Acute Phase Serum

Abstract: The complement system is regarded as an important component of the innate defence system against invading bacteria. However, synergistic actions between the complement and the other components of innate immunity are incompletely known. Human group IIA phospholipase A 2 (hGIIA PLA 2 ) is an effective antibacterial enzyme in serum of patients with severe bacterial infections. Our aim was to investigate the significance of complement and hGIIA PLA 2 in acute phase serum. Serum samples were collected from patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…Participation of sPLA 2 s in host defense, either as major antibacterial factors or as biologically active molecules modulating immune or inflammatory responses, has been documented in animal cells (25,26). Experimental evidence of the involvement of sPLA 2 s in plant defense is, in contrast, more limited.…”
Section: Discussionmentioning
confidence: 99%
“…Participation of sPLA 2 s in host defense, either as major antibacterial factors or as biologically active molecules modulating immune or inflammatory responses, has been documented in animal cells (25,26). Experimental evidence of the involvement of sPLA 2 s in plant defense is, in contrast, more limited.…”
Section: Discussionmentioning
confidence: 99%
“…GIIA sPLA 2 is predominantly recognized as part of the innate immune system and appears to be a major antibacterial factor against Gram-positive bacteria in human acute phase serum [60][61][62]. A study of patients with sepsis showed that of the nine human sPLA 2 's, only GIIA sPLA 2 could be detected in serum by time-resolved fluoroimmunoassay [63].…”
Section: Host Defensementioning
confidence: 98%
“…[23], lung [25], liver, spleen, kidney, and ovary [30], brain [31] Digestion of dietary PLs [23], antibacterial [65], eicosanoid formation, cell contraction, proliferation [30], migration [11] PG > PS >> PC [44] M-type [40] II A Acute phase serum, intestinal mucosa, lacrimal gland cells, prostatic epithelial cells [36] Acute phase protein [1,35], antibacterial [60][61][62][64][65][66], cell proliferation [3,4], migration [5], apoptosis [6], atherogenic [124] PG > PS >> PC [44] M-, N-type [40] HSPG [41] C Pseudogene (human) [18] Testis, pancreas (mouse) [44] N/D PG >> PC [44] Low affinity to M-type [ High molecular weight [20]. Antiviral [78] PG > PC [44] Low affinity to M-type [40] V Heart, eye, pancreas [44], macrophages [99], neutrophils [69], mastocytes [70] Antibacterial [17,65], antiviral [77], atherogenic [137,142], AA release, eicosanoid generation …”
Section: Introductionmentioning
confidence: 99%
“…a) 1 Unit: μmole of fatty acid released per min using egg yolk as substrate in the presence of 10 mM NaTDC and in the presence of 10 mM CaCl 2 .b) Proteins were estimated by Bradford method [30]. The experiments were conducted in triplicate.…”
Section: Resultsmentioning
confidence: 99%